ANALISIS KUALITAS TES UNTUK MENGUKUR PRESTASI BELAJAR SISWA - Junaidah (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2019)
Tests are a series of questions or exercises that are used to measure skills, knowledge, intelligence, abilities or talents possessed by individuals or groups. A test is said to be of quality if it meets the requirements, namely validity, reliability, objectivity, practice, and economics. Determining the validity of the test using the Product Moment correlation formula, to determine whether the overall test in the form of choice is reliable is used Spearman-Brown formula, while to determine the reliability of the test in the form of essay used the formula of variance. Learning achievement is the result achieved by students during the teaching and learning process. In learning a teacher must understand the subject matter and also must be able to carry out evaluation (assessment) through the right and correct procedures. Therefore, each teacher must understand how the test criteria are correct and correct in order to measure student achievement well.